A rare case of Streptococcus pneumoniae urinary tract infection in a chronic hemodialysis patient - Mehmet Biricik; Fatma Sena Türkdoğan (Intercontinental Journal of Internal Medicine, 2026)
We report a rare case of urinary tract infection (UTI) caused by Streptococcus pneumoniae in a chronic hemodialysis (HD) patient with a long-standing tunneled dialysis catheter. A 28-year-old female on thrice-weekly HD developed dysuria accompanied by genital pruritus. Urinalysis demonstrated leukocytosis and hematuria, and urine culture yielded S. pneumoniae. She had no systemic signs of infection but exhibited elevated C-reactive protein (CRP) levels. Based on antimicrobial susceptibility testing, a 7-day course of ceftriaxone resulted in culture negativity. This case highlights the need to consider unusual pathogens in UTIs with complex urogenital risk factors.